2016
DOI: 10.1007/s00464-016-4861-6
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate plus propofol versus propofol alone for sedation during gastroscopy: a randomized prospective clinical trial

Abstract: Etomidate plus propofol had few effects on respiration and circulation in patients undergoing gastroscopy and was more safe and effective than propofol alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 36 publications
1
34
1
Order By: Relevance
“…Of 10 studies that compared arrhythmia rates, four studies reported the rate of bradycardia . The combined results showed no evidence for a difference (RR, 1.59; 95% CI, 0.75 to 3.35; P chi 2 = 0.042; I 2 = 44.59%; NNTH = 386.3; 95% CI, NNTH 25.6 to ∞ to NNTB 29.5).…”
Section: Resultsmentioning
confidence: 95%
“…Of 10 studies that compared arrhythmia rates, four studies reported the rate of bradycardia . The combined results showed no evidence for a difference (RR, 1.59; 95% CI, 0.75 to 3.35; P chi 2 = 0.042; I 2 = 44.59%; NNTH = 386.3; 95% CI, NNTH 25.6 to ∞ to NNTB 29.5).…”
Section: Resultsmentioning
confidence: 95%
“…Personalized medicine could have reduced the risk of hypoxia and excessive sedation in the P group. Therefore, just as Zhou et al [15] reported, etomidate plus propofol had few effects on respiration and circulation in patients undergoing gastroscopy and were safer and more effective than propofol alone.…”
Section: Discussionmentioning
confidence: 99%
“…Etomidate plus propofol had few effects on respiration and circulation in patients, and was safer and more effective than propofol alone. [15] However, the effect and the optimal dose of propofol to minimize side effects are not well established. Thus, this study investigated the effect of pretreatment with different doses of propofol on etomidate-related myoclonus in patients scheduled for painless gastroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has shown that the physical and chemical properties of the admixture of propofol and etomidate have not changed, it can be safely used in clinical anesthesia, and its compatibility is stable. [ 11 ] Many researches have confirmed that the admixture of propofol and etomidate not only maintains the stability of the respiratory system of patients, but also reduces the incidence of adverse reactions such as injection pain, nausea and vomiting, [ 12 ] hypoxemia, [ 13 ] hypotension and oxygen desaturation. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%